Transforming growth factor β1polymorphism and serum levels in Egyptian patients with interstitial lung diseases - Rania Mohammed Azmy; Rana Helmy El Helbawy; Ashraf Abd El Raouf Dawood; Sami El Dahdaouh (Egyptian Journal of Chest Disease and Tuberculosis, 2017)
Background: Interstitial lung diseases (ILD) are a heterogeneous group of diffuse parenchymal disorders characterized by different grades of fibrosis and inflammation. A number of proinflammatory and profibrotic extracellular mediators have been implicated in the pathogenesis of ILD. Transforming growth factor beta 1(TGF-β1) is one of these mediators. Objective: The study aimed to investigate the association between two common polymorphisms in the gene encoding TGF-β1 and the risk for the development of ILD and whether those polymorphisms affect the serum level of TGF-β1 or have a relation with disease prognosis. Subjects and methods: The study included 90 subjects who were classified into: 56 patients suffering from ILD and 34 healthy subjects served as controls. Pulmonary function tests, arterial blood gases, serum levels of TGF-β1 were determined for all subjects. Genotyping for codon 10 and codon 25 polymorphisms by PCR-RFLP analysis was performed to be correlated with the serum and bronchoalveolar lavage (BAL) levels of TGF β1 and disease prognosis. Results: The allele frequencies of both polymorphisms showed no significant differences between patients and controls. However the CC genotype of codon 10 polymorphism showed significant correlation with higher levels of serum and BAL TGF-β1 and worse prognosis of the disease. Conclusion: It could be concluded that there is no significant association between codon 10 and codon 25 polymorphisms of TGF-β1 and the risk for development of ILD while there was an association between the genetic variants of codon 10 polymorphism, the serum and BAL levels of TGF-β1 and the prognosis of the disease.